Experiments Studying the Instability Process of a Subway Tunnel in Soil–Rock Composite Strata Influenced by Defects - Ruichuan Zhao; Yunfei Zheng; Yongjian Guo; Shaoshun Luan; Sulei Zhang (Buildings)
Subway tunnels excavated in soil–rock composite strata face great challenges due to the prevalence of inner defects. The instability of tunnels in these strata poses significant risks to construction safety. In this paper, indoor experiments are adopted to study the instability process of a subway tunnel in soil–rock composite strata influenced by inner cavities. A total of six groups of tests are designed based on the location of the cavity and the distance of the cavity from the tunnel. High-resolution monitoring techniques are employed to capture the real-time deformation and failure process of strata. The results show that a cavity in the strata significantly affects the stability of the strata after the tunnel excavation. The existence of a cavity increases ground deformation, and a cavity at different locations affects ground deformation. The strata around the cavity are the first to experience failure by the upper loads applied after the tunnel is excavated. The location of the cavity changes the stress distribution state of the strata and thus alters the emergence of cracks, which finally disturbs the collapse process and pattern of the composite strata. The probability and collapse range increase when the tunnel excavation impact zone is connected with the cavity weakening zone. The findings can provide technical support for the collapse prevention and safety control of subway tunnels in composite strata with internal defects.